Optimal Expectations and Limited Medical Testing: Evidence from Huntington Disease - Oster, Emily; Shoulson, Ira; Dorsey, E. Ray (The American economic review, 2013)
We use novel data to study genetic testing among individuals at risk for Huntington disease (HD), a hereditary disease with limited life expectancy. Although genetic testing is perfectly predictive and carries little economic cost, presymptomatic testing is rare. Testing rates increase with increases in ex ante risk of having HD. Untested individuals express optimistic beliefs about their health and make decisions (e.g., retirement) as if they do not have HD, even though individuals with confirmed HD behave differently. We suggest that these facts can be reconciled by an optimal expectations model (Brunnermeier and Parker 2005).